The Psychic Life and Creativity of the Forms of Life. Some Remarks on Wittgenstein’s Philosophy of Psychology - La Licata, Emiliano (Revista de Filosofía, 2015)
Wittgenstein’s later philosophy addresses the subject of connection between the psychic life of the individual and social context, represented by language games which are played within a form of life. Sensations and passions are part of the psychic life of the individual; far from being hidden psychological objects of a private Cartesian, they are inseparable from their social redefinition. In fact, they become visible in the context of the game. Wittgenstein argues that there is a transformation of subjective psychic life by learning language games. The psychic life of the individual is then re-organized by learning a socially defined, characteristic behaviour pattern. However, the learning process of the games is complex and non-deterministic, in that it oscillates between degrees of acceptance and degrees of negation of language game rules. Through this oscillation between acceptance and denial of the game rules, it is possible to develop processes which lead to unpredictable changes in the game and in forms of life.